Improving Patient Experience in Outpatient Clinics through Simulation: A Case Study - Abdullah Alrabghi; Abdullah Tameem (Modelling)
This research aims to present a case study on the use of simulation to support operational decision-making and improve the patient experience in outpatient clinics. A simulation model was developed to represent patient flow through the endocrine clinics of the internal medicine department in a large hospital in Saudi Arabia. The research evaluated the impact of using simulation models on different aspects of healthcare facility operations, such as patient flow, resource utilization, and staffing. Potential bottlenecks and inefficiencies in the clinic’s processes were identified. Furthermore, improvements were suggested and evaluated that could significantly reduce patient waiting times and increase the number of patients served. Different scenarios and strategies were evaluated without the need for real-world implementation, which can be costly and time consuming. The model can also be easily modified and adapted to accommodate changes in patient demand, staffing levels, or other factors that may impact clinic operations. The findings demonstrate the utility of simulation models in healthcare management. Overall, the use of simulation models in healthcare management has the potential to revolutionize the way clinics and hospitals operate, leading to improved patient outcomes and more efficient use of resources.